2002
DOI: 10.1159/000063379
|View full text |Cite
|
Sign up to set email alerts
|

Allergic Contact Dermatitis from Cosmetics

Abstract: Background: Cosmetics have been used since the oldest known civilisations, and nowadays almost everybody resorts to beauty products. Objective: Considering the increasing incidence of contact dermatitis, the aim of the study is to determine the impact of allergy to cosmetics. Methods: From January 1998 to December 1999, 819 patients were subjected to epicutaneous tests for suspicion of allergic contact dermatitis (ACD). The results were analysed retrospectively in the total population and in that of children u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(22 citation statements)
references
References 27 publications
2
20
0
Order By: Relevance
“…Perfumes (fragrance mix and balsam of Peru) were the most common type of allergens closely followed by preservatives, making cosmetics as the most frequent source of allergy. Few years back, Kohl [26] predicted that cosmetics could be the most common allergen in the near future and our study proved that his prediction was correct and relevant in the Indian context also. Nine cases of heterotransfer of allergen indicated that children of this region were quite at risk to the exposure to parents' cosmetics.…”
Section: Discussion Discussionsupporting
confidence: 59%
“…Perfumes (fragrance mix and balsam of Peru) were the most common type of allergens closely followed by preservatives, making cosmetics as the most frequent source of allergy. Few years back, Kohl [26] predicted that cosmetics could be the most common allergen in the near future and our study proved that his prediction was correct and relevant in the Indian context also. Nine cases of heterotransfer of allergen indicated that children of this region were quite at risk to the exposure to parents' cosmetics.…”
Section: Discussion Discussionsupporting
confidence: 59%
“…In a previous study in Rotterdam, the most positive patch test reactions in children aged 5–15 years were to nickel, cobalt and balsam of Peru [8]. However, in the study by Kohl et al [16], metals (predominantly nickel) were listed only in third place, behind cosmetics and topical drugs as the cause of ACD in children. Even legislative measures have been implemented in order to reduce exposure to nickel.…”
Section: Discussionmentioning
confidence: 99%
“…As some chemicals are recognised to be contact allergens and are withdrawn from use, they may be replaced by other products that could potentially induce contact allergy, and so the repertoire of potential allergens is constantly evolving. [15][16][17] Data from the THOR-EPIDERM project, a national occupational health surveillance scheme, has shown that the highest risk professions for developing contact dermatitis are florists, hairdressers, beauticians, cooks, metalworkers, and other manufacturing and healthcare related occupations. 18 Healthcare workers seem to be at risk because of frequent hand washing.…”
Section: Who Gets Contact Dermatitis?mentioning
confidence: 99%